An overview of late-stage functionalization in today's drug discovery. (2nd November 2019) - Moir, Michael; Danon, Jonathan J.; Reekie, Tristan A.; Kassiou, Michael
ABSTRACT: Introduction : Late-stage functionalization (LSF) can introduce important chemical groups in the very last steps of the synthesis. LSF has the potential to speed up the preparation of novel chemical entities and diverse chemical libraries and have a major impact on drug discovery. Functional group tolerance and mild conditions allows access to new molecules not easily accessible by conventional approaches without the need for laborious de novo chemical synthesis. Areas Covered : A historical overview of late-stage functionalization and its applicability to drug discovery is provided. Pioneering methodologies that laid the foundations for the field are briefly covered and archetypal examples of their application to drug discovery are discussed. Novel methodologies reported in the past few years mainly stemming from the recent renaissances of photoredox catalysis and radical chemistry are reviewed and their application to drug discovery considered. Expert opinion : It is envisioned that late-stage functionalization will improve the efficiency and efficacy of drug discovery. There is evidence of the widespread uptake of LSF by the medicinal chemistry community and it is expected that the recent and continuing endeavors of many academic laboratories and pharmaceutical companies will soon have an impact on drug development.